Transcription factor 3 (TCF3) combined with histone deacetylase 3 (HDAC3) down-regulates microRNA-101 to promote Burkitt lymphoma cell proliferation and inhibit apoptosis. Issue 1 (1st January 2021) - Dong, Lihua; Huang, Jingjing; Zu, Peng; Liu, Jing; Gao, Xue; Du, Jianwei; Li, Yufu
ABSTRACT: To explore the function of transcription factor 3 (TCF3) on the proliferation and apoptosis of Burkitt lymphoma cells and its mechanism. qRT-PCR was performed to determine the expression of TCF3, histone deacetylase 3 (HDAC3), and microRNA-101 (miR-101) in the Burkitt lymphoma (BL) tumor tissues and lymph node tissues with reactive lymph node hyperplasia (RLNH). We found that the expression of TCF3 and HDAC3 was up-regulated in BL tumor tissues and lymphoma cells, and the miR-101 expression was down-regulated. And TCF3 and HDAC3 were negatively correlated with the expression of miR-101, respectively. In addition, knockdown of TCF3 can inhibit BL cell proliferation, reduce cell viability and promote cell apoptosis, retain the cell cycle in the G0/G1 phase, and inhibit the expression of Akt/mTOR pathway-related proteins (p-Akt and p-mTOR). When miR-101 was overexpressed, the results were the same as when TCF3 was knocked down. Moreover, we used Co-immunoprecipitation (Co-IP) to detect the interaction between TCF3 and HDAC3, and performed the Chromatin immunoprecipitation (ChIP) experiment to detect the enrichment of TCF3 and HDAC3 in the promoter region of miR-101. We found that TCF3 can interact with HDAC3 and is enriched in the miR-101 promoter region. In conclusion, TCF3 combined with HDAC3 down-regulates the expression of miR-101, thereby promoting the proliferation of BL cells and inhibiting their apoptosis.